The role of gender and self-esteem as moderators of the relationship between stigma and psychological distress among infertile couples. Issue 10 (26th November 2021) - Fang, Mei; Li, Guopeng; Kang, Xiaofei; Hou, Fangyan; Lv, Gaorong; Xu, Xiaofang; Kong, Linghua; Li, Ping
ABSTRACT: To determine if perceived stigma is positively associated with psychological distress, and examine if self-esteem has a moderating effect on the relationship between stigma and psychological distress among infertile Chinese couples. 369 infertile couples completed questionnaires including socio-demographic and clinical characteristics, stigma, self-esteem, and psychological distress. Stigma had a significant, positive association with psychological distress (r = 0.461, P < 0.01). Self-esteem moderated the association between stigma and psychological distress differently for men compared to women. Stigma had a positive, moderate association with psychological distress in men with high self-esteem compared to men with low self-esteem (t = 3.232, P < 0.01). However, there was no significant difference in the relationship between stigma and psychological distress between women with high and low self-esteem, tests of the simple slopes showed that non-significant difference of slopes between the two groups (t = −0.017, P = 0.987). The results indicate that self-esteem buffers the net effect of stigma on psychological distress in men but not women. Future research should focus on interventions that use self-esteem as a way to decrease the negative association of stigma with psychological distress, especially among men who are infertile and have low self-esteem.